Rasch analysis: psychometric properties of Malaysian secondary school students’ leadership scale - Pang, Vincent Ah Fook; Mei, Teng Ling (Serial Publications Pvt.Ltd., 2016)
The purpose of this study is to produce empirical evidence of psychometric properties of a survey questionnaire, the Malaysian Secondary School Students’ Leadership Scale (M3SLS) Version 2. The scale was analysed by using Rasch Model. The questionnaire was administered on 2340 students from 26 government schools in four main divisions of Sabah, Malaysia. The results showed that secondary dimension is noticeable and the constructs were suggested to be analysed separately in future. PTMEA Corr are all in positive values. Person statistics (separation>2; reliability >0.8) and item statistics (separation>3; reliability >0.8) were within the acceptable range. All items in the M3SLS were in the range of 0.5 to 1.50, except item V5 (2.01), item V3 (1.64), item V4 (1.63), item V1 (1.63) and item V7 (1.53). All the items were maintained after the test.